AZOSPIRILLUM STRAINS AS BIOFERTILIZERS AND BIOCONTROL AGENTS -A PRACTICAL REVIEW (JOURNAL OF ADVANCES IN AGRICULTURE, 2017)
Azospirillum biofertilizers have a history going back to the beginning of the XXth However, researches still have to find new and competitive strains and improve biofertilizers production and application techniques. They are one of te most used biofertilizers in organic farming. The present paper review and analyses the development of the new agriculture using such microorganism, and showing not only the biofertilization effect but some biocontrol properties of the presented strains. The products containing Azospirillum strains and their use begin to play an important role in modern agriculture and in special in some countries in course of development as an alternative to chemical expensive and some time not environmental friendly products. Countries from Asia, South America, use it in huge quantities. In developed area of the lobe, there are only some tiny initiative, mainly because the multinational companies, and because of the legislation in use.